In vitro inhibitory effects of farnesol and interactions between farnesol and antifungals against biofilms of Candida albicans resistant strains. Issue 4 (21st April 2017) - Xia, Jinping; Qian, Fang; Xu, Wenqian; Zhang, Zhenzhen; Wei, Xin
Abstract: Antifungal resistance is a serious problem in clinical infections. Farnesol, which is a potential antifungal agent against biofilms formed by Candida albicans resistant strains (a fluconazole-resistant isolate derived from SC5314 and two clinical Candida resistant isolates), was investigated in this study. The inhibitory effects of farnesol on biofilms were examined by XTT assay. The morphological changes and biofilm thicknesses were analyzed by scanning electron microscopy and confocal laser scanning microscopy, respectively. Additionally, the checkerboard microdilution method was used to investigate the interactions between farnesol and antifungals (fluconazole, amphotericin B, caspofungin, itraconazole, terbinafine and 5-flurocytosine) against biofilms. The results showed decreased SMICs of farnesol and thinner biofilms in the farnesol-treated groups, indicating that farnesol inhibited the development of biofilms formed by the resistant strain. Furthermore, there were synergistic effects between farnesol and fluconazole/5-flurocytosine, while there were antagonistic effects between farnesol and terbinafine/itraconazole, respectively, on the biofilms formed by the resistant strains.